Cortical Auditory Evoked Potentials in 2-Year-Old Subjects - Costa,Inaê (2020)
Abstract Introduction Cortical auditory evoked potentials (CAEPs) can be used to evaluate both peripheral and cortical components of auditory function, and contribute to the assessment of functional sensitivity and auditory thresholds, especially in neonates and infants. Auditory evoked potentials reflect auditory maturity and precede the acquisition of more complex auditory and cognitive skills, and are therefore crucial for speech and language development. Objective The aim of the present study was to determine the presence, latency and amplitude of CAEP components in response to verbal stimuli in children aged 2 years old. Methods The sample consisted of 19 subjects, 10 of whom were male while 9 were female. All of the participants were 24 months old at the time of assessment. Results A total of 17 of the participants displayed all components of the CAEP. Additionally, no significant differences were observed between genders or ears in the present sample. The presence of all components of the CAEP in subjects aged 2 years old confirms the existence of a critical period for the maturation of auditory pathways in the first 2 years of life. Conclusion In the present study, in addition to the P1/N1 components, it was possible to observe the presence of the CAEP P2/N2 components in individuals aged 24 months, confirming the existence of a critical period for the maturation of the auditory pathways in the first 2 years of life.